Transurethral holmium laser vaporization to the urethral tumour through a ureteroscope - Li, Aihua; Fang, Wei; Zuo, Xiaoming; Zhang, Feng; Li, Weiwu; Lu, Honghai; Liu, Sikuan; Wang, Hui; Zhang, Binghui (Canadian Urological Association Journal, 2014)
We present 2 cases of urethral cancers: one is recurrent bladder transitional cell carcinoma accompanied by urethral metastatic carcinoma located on the right side of verumontanum, and the other is primary bladder and metastatic urethral adenocarcinoma. The urethral tumour was treated by transurethral holmium laser vaporization to the urethral tumour through a ureteroscope and the bladder tumour was treated with transurethral resection and degeneration of the bladder tumour (TURD-Bt). After the second or third therapy, patients were free of urethral or bladder tumour recurrence; they also did not experience urethral stricture or urinary incontinence during the 24- to 36-month follow-up. Transurethral holmium laser vaporization and TURD-Bt could be performed to treat non-invasive urethral cancer accompanied with bladder cancer and preserve the urethra and bladder.